Thin film micro-scaled cold cathode structures of undoped and Si-doped AlN grown on SiC substrate with low turn-on voltage - 侍铭 陈平 赵德刚 江德生 郑军 成步文 朱建军 刘宗顺 刘炜 李翔 赵丹梅 王启明 刘建平 张书明 杨辉 (Chinese physics B, 2015)
The field emission characteristics of the AlN thin films with micro-scaled cold cathode structures are tested in the high vacuum system. The aluminum nitride （A1N） thin films with a thickness of about 100 nm are prepared on the n-type 6H-SiC （0001） substrate at 1100℃ by metal organic chemical vapor deposition （MOCVD） under low pressure. The I-V curves and surface micro-images of undoped and Si-doped AlN films are investigated. From the I-V and Fowler-Nordheim plots, it can be seen that the Si-doped AlN shows better field emission characteristics compared with the undoped AlN sample. The obtained turn-on field is 6.7 V/μm and the maximum emission current density is 154 mA/cm2 at 69.3 V for the Si- doped AlN film cathode after proper surface treatment. It is proposed that the relatively low electric resistivity of Si-doped AlN films is significant for electron migration to the surface region, and their rougher surface morphology is beneficial to a higher local electric field enhancement for the field emission.